Efektivitas Relaksasi Napas dalam Terhadap Kecemasan pada Pasien Pra Operasi Open Reduction & Internal Fixation dengan Fraktur Ekstermitas Bawah Rumah Sakit Mary Cileungsi Hijau - Said, M Irhas; Darma, Alfunanto Dlifa Puji; Sahrudi, Sahrudi (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT The 2022 WHO report noted that there are 440 million people with fractures globally. Fractures, often caused by excessive pressure, interfere with daily mobility. SKI 2023 data shows that in Indonesia, 50.6% of the population ≥1 year use walking aids, 25.5% due to accidents causing walking disabilities of 0.4%, which lasts at least six months according to Law No. 8 of 2016. Objective: To determine and analyze the Effectiveness of Deep Breathing Relaxation on Anxiety in Preoperative Open Reduction Internal Fixation Patients with Lower Extremity Fractures at Mary Cileungsi Hijau Hospital. To determine and analyze the Effectiveness of Deep Breathing Relaxation on Anxiety in Preoperative Open Reduction Internal Fixation Patients with Lower Extremity Fractures at Mary Cileungsi Hijau Hospital. This study used a quasi-experimental method with a pre-test post-test design in one group at Mary Cileungsi Hijau Hospital, Bogor, from November 2024 to January 2025. The population of this study was 40 patients selected through total sampling. There is an effect between deep breathing relaxation on anxiety in preoperative Open Reduction Internal Fixation patients with lower extremity fractures at Mary Cileungsi Hijau Hospital with a P-Value of 0.000. The majority of patients undergoing Open Reduction Internal Fixation surgery for lower extremity fractures are young to middle-aged adult males, covering 75% of the total patients. Deep breathing relaxation techniques have been shown to significantly reduce anxiety, with a p-value of 0.000, indicating a significant difference in anxiety scores before and after the intervention. Keywords: Deep Breathing Relaxation, Anxiety, Preoperative Open Reduction, Internal Fixation, Extremity Fractures.  ABSTRAK Laporan WHO 2022 mencatat ada 440 juta orang dengan fraktur global. Fraktur, sering disebabkan oleh tekanan berlebih, mengganggu mobilitas sehari-hari. Data SKI 2023 menunjukkan di Indonesia, 50,6% penduduk ≥1 tahun menggunakan alat bantu berjalan, 25,5% akibat kecelakaan yang menyebabkan disabilitas berjalan sebesar 0,4%, yang berlangsung minimal enam bulan sesuai UU No. 8 Tahun 2016. Mengetahui dan menganalisis Efektivitas Relaksasi Napas Dalam Terhadap Kecemasan Pada Pasien Pra Operasi Open Reduction Internal Fixation dengan Fraktur Ekstermitas Bawah Rumah Sakit Mary Cileungsi Hijau. Penelitian ini menggunakan metode quasi eksperimental dengan desain pre-test post-test pada satu kelompok di Rumah Sakit Mary Cileungsi Hijau, Bogor, dari November 2024 hingga Januari 2025. Populasi penelitian ini adalah 40 pasien yang dipilih melalui total sampling. Terdapat pengaruh antara relaksasi napas dalam terhadap kecemasan pada pasien pra operasi Open Reduction Internal Fixation dengan fraktur ekstermitas bawah di Rumah Sakit Mary Cileungsi Hijau dengan P-Value 0.000. Mayoritas pasien operasi Open Reduction Internal Fixation untuk fraktur ekstremitas bawah adalah laki-laki dewasa muda hingga paruh baya, mencakup 75% dari total pasien. Teknik relaksasi napas dalam terbukti secara signifikan menurunkan kecemasan, dengan p-value 0.000, yang menunjukkan perbedaan besar dalam skor kecemasan sebelum dan sesudah intervensi. Kata Kunci: Relaksasi Napas Dalam, Kecemasan, Pra Operasi Open Reduction, Internal Fixation, Fraktur Ekstermitas.